Design of inorganic–organic hybrid photocatalytic systems for enhanced CO2 reduction under visible light. (2nd November 2019) - Zhang, Lu; Wang, Wei; Wang, Hui; Ma, Xin; Bian, Zhaoyong
Graphical abstract: Highlights: Mn complex is anchored on Bi2 WO6 particle with bisphosphonate functional groups. Inorganic–organic binary system gives low-cost and efficient reduction of CO2 . H-Bi2 WO6 /MnP photocatalytic CO2 exhibits high product selectivity and productivity. This process provides new industrialized possibilities for photocatalytic CO2 . Abstract: The photocatalytic conversion of CO2 to renewable hydrocarbon fuels by solar energy is important in solving both energy and environmental problems. In this study, highly robust hybrid systems (H-Bi2 WO6 /MnP, F-Bi2 WO6 /MnP, and T-Bi2 WO6 /MnP) for visible-light reduction of CO2 to CO were developed. A Mn complex was anchored to Bi2 WO6 particles via bisphosphonate functional groups. Photocatalytic CO2 reduction with this catalytic system under visible-light ( λ > 400 nm) irradiation was investigated. CO was the only product, i.e., no other products were detected in the present system. The addition of water or triethylamine significantly enhanced the CO2 conversion activity of the hybrid photocatalytic system. The addition of 25% (v/v) water enhanced the photocatalytic CO2 reduction efficiency of H-Bi2 WO6 /MnP. A turnover number of 301 for 8 h was achieved, compared with 255 for F-Bi2 WO6 /MnP and 212 for T-Bi2 WO6 /MnP. The Mn complex played an important role in achieving highly selective conversion of CO2 to CO. A possible mechanism, namely a "Z-scheme", for CO2 reduction is proposed. These results confirm that the H-Bi2 WO6 semiconductor is an essential component in our heterogeneous hybrid system. It effectively acts as a photosensitizer, an electron reservoir, and an electron transport mediator.